Pendampingan Orang Tua terhadap Proses Belajar Secara Daring Selama Masa Pandemi - Rosita Nugraheni Kusumaningrum (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2021)
This study aims to determine Parental Assistance in the Online Learning Process during the Pandemic Period of Class VI students at SD Negeri Kedungsari 2 Magelang. This research uses descriptive qualitative research. The sample in this study used purposive sampling, which consisted of 15 parents of fourth grade students at SD Negeri Kedungsari 2 Magelang. The data collection method used three methods, namely observation to parents, interviews with teachers and students, and questionnaires for parents. The data validity technique used is source triangulation and technical triangulation. The results showed that parental assistance had been going well during the pandemic. This is evidenced by a questionnaire which shows that 90% of parents have provided learning facilities, 91% have assisted in the use of study time, 82% have assisted in solving learning difficulties, 79% have provided motivation to learn, 85% have accompanied and accompanied learning, and 71 % have successfully faced the obstacles experienced in learning. Based on this research, it can be concluded that parents have implemented learning assistance very well based on the agreed protocol.